EFFECT OF GREEN SUPPLY CHAIN PRACTICES ON PERFORMANCE OF LARGE CHEMICAL MANUFACTURING FIRMS IN NAIROBI COUNTY KENYA - Mutisya, Fredrick Masai; Kinoti, Dr. Justus (International Journal of Supply Chain Management, 2017)
Purpose: Social and political concerns about the environment in Kenya have increased in the recent years. Recently, they year 2017, the Kenyan government has established a new environmental management and natural resources Act, this study acknowledges that the that success in the environmental protection can contribute to the building of a positive image for customers and provide many new opportunities to expand business thus improving the overall performance of a firm. The growing importance of GSCM are driven mainly by the escalating deterioration of the environment for instance diminishing raw material resources, overflowing waste sites and increasing levels of pollution. Therefore, there was need to establish the effect of GSCM practices on performance and provide policy recommendations that can help salvage the poor performance recently witnessed in the manufacturing sector. The study specifically focused on green purchasing practices, waste management practices, green distribution practices and ICT. Methodology: This study adopted a descriptive survey design. The target population consisted of 63 large chemical manufacturing firms licensed by the Kenya Association of manufacturers. The data collection instrument was a questionnaire and secondary data collection template. The study used correlation and regression to achieve the specific objectives. Findings: The study findings showed that green purchasing practices, waste management practices, ICT and green distribution practices positively and significantly influence the performance of large chemical manufacturing firms in Kenya. Policy recommendation: The study recommends large chemical manufacturing firms in Kenya to ensure they have green manufacturing system. There is also need for manufacturing firms to have well-established environmental compliance policies. There is also need to have technological support for the design of recyclable products. Further there is need for the manufacturing firms to conduct the distribution of their products using returnable packaging materials.